Dodecylamine-Induced Synthesis of a Nitrogen-Doped Carbon Comb for Advanced Lithium-Sulfur Battery Cathodes - Lu, Q.; Zhong, Y.; Zhou, W.; Liao, K.; Shao, Zongping (Wiley-VCH Verlag, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Host materials that can provide both a strong absorbability of soluble intermediate polysulfides and a high electronic conductivity are in high demand to realize practical applications of Li-S batteries. Here, the rational design of an N-doped carbon comb (NCC) as a new type of sulfur host for Li-S batteries, delivering a favorable performance, particularly a good cycling stability and rate capability, is reported. A novel dodecylamine micelle-induced self-assembling method is first proposed for constructing the NCC host which is built from close-packed hollow submicron carbon spheres. The interconnected carbon frameworks create good electrical conductive pathways. In addition, the high porosity and the N doping of the NCC host effectively suppress sulfur losses during cycling through synergistic physisorption and chemisorption effects. As a result, cathodes with 71 wt% of sulfur deposited in the NCC host possess superior capacities of 1090 and 553 mAh g -1 at 0.1 and 2 C, respectively. After 300 cycles at 1 C, a reversible capacity of 562 mAh g -1 is retained. Even at a high sulfur loading of 83 wt%, favorable performance is realized.